Effect of the thermal state during Manila mango processing by mild flash vacuum-expansion on carotenoids and enzymatic activity. (January 2022) - Marin-Castro, U.R.; Dominique, P.; García-Alvarado, M.A.; Vargas-Ortiz, M.A.; Salgado-Cervantes, M.A.; Servent, A.
Abstract: Flash vacuum-expansion (FVE) was assessed as an alternative to conventional techniques for Manila mango processing, which is a highly perishable variety. Methodology: The impact of different thermal exposure times, followed by cold storage, on carotenoids, enzymatic activity of polyphenol oxidase (PPO) and peroxidase (POD), as well as antioxidant and color properties was evaluated. Results and discussion - an increase in heat intake promoted the isomerization of all-trans into all-cis forms but allowed products with considerable amounts of provitamin A to be obtained, in addition to achieving complete inhibition of PPO and POD after processing. During storage, great stability of the carotenoids, a greater conservation of the antioxidant and color properties, and a partial recovery of POD activity were observed. Conclusion: FVE showed it's a viable alternative by retaining more than 58% of all-trans -β-carotene and inducing enzymatic inactivation which resulted in greater stability of quality properties of the final product. Industrial relevance: The transformation of "Manila" mango into puree is a viable alternative for the use and management of this variety, whose physiological characteristics make it highly perishable. The results obtained in the present study show the ability of the flash vacuum-expansion process (FVE) to obtain a minimally processed product, without additives, capable of preserving considerable contents of carotenoids, as well as provitamin A equivalents, also achieving the inactivation of endogenous enzymes responsible for deterioration of quality and an increase in color stability and antioxidant properties. The results could be used by the food industry as a basis for the application of FVE during the transformation of Manila mango, reducing postharvest losses, and allow obtaining a more stable product with greater commercial attractiveness. Highlights: Preservation of 58.94% of all-trans -β-carotene 100 g of puree is enough to cover 30% of the daily retinol requirement in women and children. Complete enzymatic inhibition of polyphenol oxidase and peroxidase after the process Increased antioxidant and color stability during storage Recovery of the peroxidase enzymatic activity during storage